A new praeaulacid genus with a new species in Praeaulacidae (Hymenoptera: Evanioidea) from mid-Cretaceous Myanmar amber. (June 2023) - Li, Longfeng; Shih, Chungkun; Yang, Jingtao; Ren, Dong
Abstract: A new fossil praeaulacid wasp, Hadraulacus perrarus Li, Shih and Ren gen. et sp. nov., is described and figured from mid-Cretaceous Myanmar amber. The new genus is established based on the following characters: antenna with more than 25 antennomeres; metasoma distinctly longer than mesosoma with the first metasomal segment forming a long petiole; legs long and thin, with tibia spurs 1-1-2, claw with one small subbasal tooth; forewing with 1cu-a postfurcal, 1m-cu shorter than 1-M and 2m-cu, 2r-m absent, 3r-m present, 2 + 3rm nearly trapezoidal, and 1m-cu in contact with 2 + 3rm by a short section of M. In addition, this mid-Cretaceous praeaulacid wasp was preserved together with a cicada nymph, likely the result of an accidental assemblage.